Taking the High Ground: FEMA Trailer Siting after Hurricane Katrina. (29th April 2013) - Aldrich, Daniel P.; Crook, Kevin
<x xml:space="preserve">Abstract</x> Using data on more than 300 census blocks from across New Orleans, Louisiana, this article investigates two steps in the placement of temporary housing after Hurricane Katrina. First, the authors seek to understand the factors that determined whether census blocks were selected for Federal Emergency Management Agency (FEMA) trailers. Then, in light of the widespread resistance to the trailers, they focus on variables that influenced whether trailers were successfully placed on those sites. Despite past research arguing that race, collective action potential, and political factors are the primary determinants of facility placement and the success or failure of the attempt, these data show that technocratic criteria dominated. Interestingly, although census blocks in less vulnerable areas were more likely to be selected as locations for FEMA trailer parks than ones in more vulnerable areas, it was precisely the former areas where siting success was less likely. Flood‐resistant areas that decision makers chose for housing were less willing to accept such projects than more flood‐prone ones.